Risk of colorectal cancer in a population-based study 20 years after diagnosis of ulcerative colitis: results from the IBSEN study. Issue 1 (26th March 2020) - Klepp, Pasquale; Brackmann, Stephan; Cvancarova, Milada; Hoivik, Marte Lie; Hovde, Øistein; Henriksen, Magne; Huppertz-Hauss, Gert; Bernklev, Tomm; Hoie, Ole; Kempski-Monstad, Iril; Solberg, Inger Camilla; Stray, Njaal; et al.
Abstract : Objective: The association between ulcerative colitis (UC) and colorectal cancer (CRC) is widely accepted, although attenuated risk has been reported in recent years. Colonoscopic surveillance is recommended with intervals based on established clinical risk factors. Nevertheless, a significant number of patients develop interval cancers, indicating the need of improved individualised assessment. In the present study, we evaluated clinical risk factors associated with CRC during a prescheduled follow-up 20 years after diagnosis, the IBSEN study. Design: A population-based inception cohort of patients diagnosed with inflammatory bowel disease from 1 January 1990 until 31 December 1993, prospectively followed at 1, 5, 10 and 20 years after diagnosis. A total of 517 patients with UC were included; 264 (51 %) men; median age at inclusion 37.4 years (4–88). Results: The overall incidence of CRC was 1.6% (8/517) at a 20-year follow-up. The total lifetime risk of CRC prior to or after UC diagnosis was 2.3%. (12/517). Patients older than 70 years at diagnosis had a 15-fold higher risk of CRC compared with those diagnosed when younger than 40 years, with HR 15.68 (95% CI: 1.31 to 187.92). Neither sex, first-degree relative with CRC, extent of colitis nor primary sclerosing cholangitis affected the risk of CRC. Conclusion: The risk of CRC in UC was low and comparable with the risk of CRC in the background population of Norway.